Examining historical thinking skills in pre-service history teachers: Challenges in Bridging theory and practice in Indonesia - Utomo, Susilo Setyo; Taneo, Malkisedek; Rahmawati, Arfita; Saefudin, Arif (Kasetsart Journal of Social Sciences, 2026)
Historical thinking skills (HTS) are an important component of history education, yet their application in pre-service teachers’ training remains challenging. This study aims to assess the level of HTS among pre-service teachers and identify the challenges they face in bridging theory and practice. This research used a qualitative method with a case study approach. The participants consisted of 65 pre-service teachers from the History Education Study Programme of Nusa Cendana University, who took a final exam with written assignments relating to analysing historical sources and applying HTS. The results showed that the majority of participants (63.08%) only reached the declarative level, while only 24.62 percent managed to reach the applicative level in HTS. The successful integration of these skills was strongly influenced by the participants’ educational background and ability to connect theory with practice. The findings show that although the participants had declarative knowledge of HTS, only a tiny proportion achieved advanced competencies. The participants reported that time constraints and lack of guidance were significant obstacles to applying skills during teaching practice. This research offers practical insights into the limitations of traditional teaching methods in fostering HTS and recommends expanding practice placements and strengthening mentorship programmes to align teacher training with the Merdeka Belajar-Kampus Merdeka (MBKM) curriculum. The research highlights the need to integrate theory and practice to develop history teachers who effectively teach HTS in Indonesia.